Artemisinin combination therapy at delivery to prevent postpartum malaria: A randomised open-label controlled trial - Paula Tesine; Sze-Ann Woon; Moses Laman; Gumul Yadi; Phantica Yambo; Bernadine Kasian; Lina Lorry; Leanne J. Robinson; Sam Salman; Kevin T. Batty; William Pomat; Laurens Manning; et al. (International Journal of Infectious Diseases)
Objectives: Although the incidence of malaria is increased in women in endemic areas after delivery compared to non-pregnant women, no studies have assessed the benefit of presumptive antimalarial treatment given postpartum. Methods: A randomised controlled trial investigating the efficacy of antimalarial treatment in preventing postpartum malaria was performed in healthy Papua New Guinea mothers immediately following delivery. Participants were randomised 1:1 to no treatment (n = 90) or artemisinin combination therapy (ACT), with further 1:1 ACT randomisation to artemether-lumefantrine (AL; n = 45) or dihydroartemisinin-piperaquine (DP; n = 45). Standardised reviews were conducted monthly for 6 months, including clinical assessment, malaria screening and haemoglobin measurement. The primary endpoint was incidence of slide-positive malaria within 6 months of delivery. Results: Of 183 recruited participants, 151 completed study procedures and were included in per-protocol analyses (no treatment n = 71, AL n = 40, DP, n = 40). Those allocated to ACT were significantly less likely to develop slide-positive malaria during the 6-month follow-up period compared to those who were untreated (n = 17 (21%) vs n = 27 (38%); P = 0.016; hazard ratio 0.49 (95% confidence intervals 0.27-0.90). There was no significant difference in malaria incidence between the two ACT groups. Conclusion: A treatment course of ACT at time of delivery halved the incidence of malaria infection during the first 6-month postpartum.